Noise induced sleep disturbance in adult population: Cross sectional study in Skopje urban centre - Gordana Ristovska; Dragan GJorgjev; Elisaveta Stikova; Vera Petrova; Marina Davceva (Institute od Immunobiology and Human Genetics, Faculty of Medicine, University "Ss Kiril and Metodij", Skopje, 2009)
Aim. To evaluate sleep disturbance caused by environmental noise in residents of Skopje urban centre and to quantify the probability for sleep disturbance related to night-time noise exposure. Methods. Cross sectional study with noise measurements for determination of noise exposure indicator Lnight. A randomised sample was selected from adult population and directly interviewed with questionnaire for assessment of sleep disturbance. Results. 510 questionnaires were collected and the response rate was 72%, 8% of the population sample reported a high level of sleep disturbance and 18% reported a moderate level of sleep disturbance. The most frequent sources of noise were neighbourhood and road traffic. The most disturbed age group were individuals 51-65 years old, who were significantly more disturbed (p=0.010) than the age group of 41-50 years old. Differences in sleep disturbance were significant only for the group exposed to Lnight ≥ 56 dBA (Wald = 4.31; p = 0.04). Exposure to Lnight above 56 dBA had OR = 2.2 (95% CI 1.1 - 4.7) or double significant increase probability for sleep disturbance, compared with control group of subjects exposed to Lnight ≤ 45 dBA. Conclusion. Night time noise exposure above the established limit values significantly increased the risk for sleep disturbance. These findings induce necessity for reducing noise exposure, especially during night-time and for taking preventive measures.
Keywords: noise; environmental exposure; sleep disorders; threshold limit values; odds ratio; public health